A minimal model of hospital patients' dynamics in COVID-19. (November 2020) - Papo, David; Righetti, Marco; Fadiga, Luciano; Biscarini, Fabio; Zanin, Massimiliano
Highlights: The region-specific modulation of COVID-19 dynamicsis characterised with a reduced exponential model leveraging available data on sub-intensive and intensive care unit patientsmade available by all regional councils from the very onset of the disease. This simple model provides a rather good fit of regional patient dynamics, particularly for regions where the affected population was large, highlightingimportant region-specific patterns of epidemic dynamics. Abstract: Italy has been one of the countries hardest hit by the coronavirus disease (COVID-19) pandemic. While the overall policy in response to the epidemic was to a large degree centralised, the regional basis of the healthcare system represented an important factor affecting the natural dynamics of the disease induced geographic specificities. Here, we characterise the region-specific modulation of COVID dynamics with a reduced exponential model leveraging available data on sub-intensive and intensive care unit patients made available by all regional councils from the very onset of the disease. This simple model provides a rather good fit of regional patient dynamics, particularly for regions where the affected population was large, highlighting important region-specific patterns of epidemic dynamics.